Forensic Autopsy in the Republic of Benin: Knowledge and Perceptions of Relatives of the Deceased - BIGOT, CÉDRIC EGNONWA PARFAIT; AGBODANDE, KOUÉSI ANTHELME; WANVOEGBE, FINANGNON ARMAND; AZON ÉPSE KOUANOU, ANGÈLE; BADOU, OLADOUN AGNES (My University, 2022)
Abstract: This study aimed to describe the knowledge of relatives of the deceased regarding forensic autopsy and to analyze their perceptions of this forensic act. The focus of the study was the relatives of deceased individuals who died in violent contexts or suffered suspicious deaths, in which case a forensic autopsy was necessary. A total of 109 people were included in the study. The majority of respondents were male (78.0%). The average age of respondents was 46 +/- 11 years. A total of 56.9% of respondents had never heard the expression "medico-legal autopsy" before the death of the relative. Respondents know. that autopsies are used to identify the cause of death in 80.7% of cases. An association was found between level of education and level of knowledge concerning forensic autopsies (p=0.001). A total of 85.3% of respondents had poor perceptions of forensic autopsy. The preservation of bodily integrity was more important than the benefits of knowing the cause of death for 57.8% of respondents. Respondents claimed that family members made at least one attempt to postpone the autopsy in 94.5% of cases. Objections to the autopsy were motivated by the fear of not being able to proceed quickly with the burial (93.6%), the fear of seeing the body undergo an aesthetic alteration (74.3%), the feeling of inflicting suffering on the deceased (45.3%) and the conception of autopsy as a practice prohibited by respondents’ religion (38.5%). The cultural and human dimensions of forensic autopsy should not be overlooked. For more support from the relatives of the deceased, it is essential to integrate, beyond medicine and law, social considerations and human. Keywords: Forensic Autopsy, Knowledge, Socio-cultural Belief, Death, Justice
Keywords: Forensic Autopsy; Knowledge; Socio-cultural Belief; Death; Justice